STRATEGI KOMUNIKASI PEMASARAN DALAM MENINGKATKAN KUNJUNGAN WISATAWAN DI DESA WISATA CIKOLELET - Nurul Aulia Dewi; Dwi Nurina Pitasari (TECHNO-SOCIO EKONOMIKA, 2024)
Cikolelet Tourism Village is a tourist village that won two awards at the 2021 ADWI event and is a pioneer in tourism villages in Serang district. The large number of tourist villages that have sprung up means that these tourist villages must create good communication strategies to be able to compete. The aim of this research is to determine the marketing communication strategies carried out by the management of the Cikolelet Tourism Village to increase tourist visits. The approach used is a qualitative descriptive approach and the method used in this research is a case study. The marketing communication strategy carried out by Pokdarwis Cikolelet was analyzed using the AIDDA model. At the awareness stage, this tourist village introduces it via social media to attract tourist interest. Furthermore, with a sense of interest, tourists can search for information and learn more about tourist villages. Then, after tourists are interested, a desire will arise to visit this tourist village. After there is a desire, tourists will make a decision to visit. In the final stage, tourists finally realize this decision by visiting a tourist village.